Over a million students use our free study notes to help them with their homework
= (4/3)x3 - (10/2)x2 + x1/2/(1/2) + C = (4/3)x3 - 5x2 + 2x1/2 + C
The idea here is to pair your numbers up to get to the solution. If you were to put this through a calculator it would take you a while. However, if we simplify the problem to the sum of 1 to 10 you'll be...
First we subtract ln(2-y) from both sides to get "ln(4y+7) - ln(2-y) = 3". By applying the laws of logs from C2, we have "ln[(4y+7)/(2-y)] = 3". Therefore, if we put them as exponents ...
Firstly I would state the substitution rule, letting 5xCos(3x)=w(x), and differentiating with respect to w(x). This gives y'(x)=2w'(x)(w(x)).I would then demonstrate the product rule stating ...
You first calculate the delta of the equation: delta = b^2-4ac = 16 - 16 = 0 => the solution is double.x1,2 = (-b±sqrt(delta))/2/a = 4/2/4 = 1/2 which is real.so the solutions are 1/2 and 1/2....
←
323
324
325
326
327
→
Internet Safety
Payment Security
Cyber
Essentials